Pain catastrophizing, but not mental health or social support, is associated with menstrual pain severity in women with dysmenorrhea: A cross-sectional survey. Issue 6 (3rd July 2022) - Evans, Subhadra; Dowding, Charlotte; Olive, Lisa; Payne, Laura A; Druitt, Marilla; Seidman, Laura C; Skvarc, David; Mikocka-Walus, Antonina
ABSTRACT: The aim of this study was to understand the relationship between psychosocial factors, including mental health, pain cognitions and social support associated with menstrual pain severity in women with dysmenorrhea of no identified medical cause (primary dysmenorrhea; PD) and dysmenorrhea related to endometriosis. Participants included 1192 women aged 18–50 years with menstrual pain, recruited to an online cross-sectional survey in 2019. Questionnaires assessed self-reported menstrual pain severity, depression, anxiety, stress, pain catastrophizing, and social support. Women with endometriosis had significantly higher menstrual pain severity (p < 0.001) and pain catastrophizing (p < 0.001) than women with PD. Of the psychosocial factors, only pain catastrophizing (specifically, the helplessness sub-scale) predicted menstrual pain severity in each group. Overall, 36% of women with PD and 58% with endometriosis had clinically relevant levels of pain catastrophizing. Findings suggest a common psychological mechanism in women with menstrual pain, regardless of etiology. Interventions to reduce pain helplessness may be beneficial in supporting women with dysmenorrhea.